LA DECONSTRUCTION DE L’EUROCENTRISME PHILOSOPHIQUE PAR LES PHILOSOPHES AFRICAINS - MOUNGA, Bauvarie (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
Deconstruction of the Philosophical Eurocentrism by African Philosophers. Eurocentrism is a current that is manifested by the refusal, disdain and depreciation of all knowledge abroad in favor of European cultures. So it is question of the promotion of Western Europe as the very center of the political, economic and philosophical thinking. Precisely, given the philosophical eurocentrism, African thinkers are trying to reach more visibility and to question this state of affairs. The purpose of this paper is to describe and analyze the different ways in which African philosophers criticize eurocentrism and to study the different philosophical currents set up to provide more visibility to African philosophy. The paper has two sections: philosophy and the cult of eurocentrism and the various means of affirmation of African philosophy. RÉSUMÉ. L’eurocentrisme est un courant qui se manifeste par le refus, le mépris et la dévalorisation des connaissances étrangères au profit des cultures européennes. Donc, il est question de la promotion de l'Europe occidentale comme le centre même de la pensée politique, économique et philosophique. Précisément, compte tenu de l'eurocentrisme philosophique, les penseurs africains essaient d'avoir une plus grande visibilité et à remettre en question cet état de chose. Le but de cet article est, de décrire et d'analyser les différentes façons dont les philosophes africains critiquent l’eurocentrisme, et d'étudier les différents courants philosophiques mis en place pour fournir plus de visibilité à la philosophie africaine. L’article comporte deux sections: la philosophie et le culte de l'eurocentrisme et les différents moyens d'affirmation de la philosophie africaine. Mots-cléfs: eurocentrisme philosophique, philosophie africaine, déconstruction, afrocentrisme, ethnophilosophie